Anti-citrullinated protein antibody titre as a predictor of abatacept treatment persistence in patients with rheumatoid arthritis: a prospective cohort study in Japan. (2nd January 2020) - Endo, Y; Koga, T; Kawashiri, S-Y; Morimoto, S; Nishino, A; Okamoto, M; Eguchi, M; Tsuji, S; Takatani, A; Shimizu, T; Sumiyoshi, R; Igawa, T; et al.
Abstract : Objective : Successful rheumatoid arthritis (RA) outcome depends on treatment efficacy in the early stages of the disease and its sustainability. It is thus critical to identify factors predicting treatment persistence with biological agents, such as abatacept. We compared clinical profiles, including early changes in autoantibody titres at 3 months, between patients with RA demonstrating sustained persistence and those discontinuing abatacept treatment. Method : We prospectively enrolled 71 and 78 active RA patients treated with abatacept and tumour necrosis factor inhibitors (TNF-Is), respectively, who had previous disease-modifying anti-rheumatic drug) failure. Clinical characteristics were compared between non-continuation and continuation groups stratified according to abatacept or TNF-I persistence for at least 12 months from treatment initiation. Results : Significantly larger decreases in rheumatoid factor titre and anti-citrullinated protein autoantibody (ACPA) titre were observed in the continuation group of abatacept therapy at 3 months, and early reduction in ACPA titre remained a significant and independent predictor of sustained persistence with abatacept in multivariate analysis. In addition, we obtained the area under the receiver operator characteristics curve of 0.904 from a model including baseline ACPA titre and reduction of ACPA titre at 3 months. Sustained reduction of RA disease activity score at 12 months was significantly and independently associated with reduced ACPA titre at 3 months. Conclusions : Persistence with abatacept and sustained therapeutic response are associated with an early reduction in ACPA titre. Prediction of abatacept continuation and efficacy will facilitate the optimal design of therapy in the early stages of RA.